2023
DOI: 10.3390/pr11041031
|View full text |Cite
|
Sign up to set email alerts
|

CNC Turning of an Additively Manufactured Complex Profile Ti6Al4V Component Considering the Effect of Layer Orientations

Abstract: Electron beam melting (EBM) is one example of a 3D printing technology that has shown great promise and advantages in the fabrication of medical devices such as dental and orthopedic implants. However, these products require high surface quality control to meet the specifications; thus, post-processing, such as with machining processes, is required to improve surface quality. This paper investigates the influence of two-part orientations of Ti6Al4V EBM parts on the CNC machining (turning) process. The two poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(45 reference statements)
2
3
0
Order By: Relevance
“…Furthermore, the minor tool feed marks are generated when the milling tool is moved perpendicular to the layers, which achieved a smaller surface roughness, as shown in Figure 6a. All of this is consistent with [19][20][21][22].…”
Section: Grey Relational Analysis (Gra) With Entropy Weights Analysissupporting
confidence: 84%
See 3 more Smart Citations
“…Furthermore, the minor tool feed marks are generated when the milling tool is moved perpendicular to the layers, which achieved a smaller surface roughness, as shown in Figure 6a. All of this is consistent with [19][20][21][22].…”
Section: Grey Relational Analysis (Gra) With Entropy Weights Analysissupporting
confidence: 84%
“…Furthermore, the minor tool feed marks are generated when the milling tool is moved perpendicular to the layers, which achieved a smaller surface roughness, as shown in Figure 6a. All of this is consistent with [19][20][21][22]. The difference in surface roughness among the three directions is because the tool interacts with a single EBM layer while machining along Direction 3 and exerts compressive forces at the EBM layer interface, which causes the bonded layers to rupture, resulting in a high surface roughness.…”
Section: Grey Relational Analysis (Gra) With Entropy Weights Analysissupporting
confidence: 73%
See 2 more Smart Citations
“…Some studies have shown that the 3D printing layer orientations considerably affect the final visual appearance of the additively manufactured parts. Milling of the Ti6Al4V [38] and γ-TiAl EBM [33] components and turning of the Ti6Al4V EBM [39] components are examples where the effects of layer orientations have been studied and published. It has been found through investigations that the same machining parameters can produce varying degrees of surface roughness depending on the orientation of the EBM component being machined [40].…”
Section: Introductionmentioning
confidence: 99%